2001
DOI: 10.1093/intimm/13.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between eosinophilia induced by CD4+ T cells and bronchial hyper-responsiveness

Abstract: The relationship between CD4(+) T cell-mediated airway eosinophilic inflammation and bronchial hyper-responsiveness (BHR) was investigated. Ovalbumin-reactive T(h)0 clones were adoptively transferred to unprimed BALB/c mice and then the mice were challenged by inhalation of the relevant antigen. Upon antigen provocation, infused T(h) clones infiltrated into the airways, followed by the accumulation and degranulation of eosinophils, goblet cell hyperplasia, edema and increase in bronchial responsiveness to acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 64 publications
3
22
0
1
Order By: Relevance
“…We have verified that allergic eosinophilic inflammation can be reconstituted by the adoptive transfer of antigenspecific Th2 clones into unprimed recipients [4,5]. Airway eosinophilic infiltration of T cell-transferred mice are dependent on IL-5 produced by the infused T cells.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…We have verified that allergic eosinophilic inflammation can be reconstituted by the adoptive transfer of antigenspecific Th2 clones into unprimed recipients [4,5]. Airway eosinophilic infiltration of T cell-transferred mice are dependent on IL-5 produced by the infused T cells.…”
Section: Introductionmentioning
confidence: 62%
“…Involvement of helper T cells in allergic eosinophilic inflammation has been demonstrated [4,5,8,12,20,21]. Activated CD4 + T cells that produce Th2 cytokines is increased in the bronchial mucosa of asthmatic patients [1,2,22,23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An immunoglobulin E/mast cell-dependent cascade has been implicated in allergic diseases [13], whereas our recent investigations clearly demonstrated that airway eosinophilic inflammation can be reconstituted in unprimed mice by the adoptive transfer of antigen-specific Th2 cells, independently of immunoglobulin E and mast cells [14, 15]. Antigen-induced lung eosinophilia in Th2-cell-transferred mice was dependent on IL-5 produced by the infused T cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Antigen-induced lung eosinophilia in Th2-cell-transferred mice was dependent on IL-5 produced by the infused T cells [14]. Furthermore, the number of accumulated eosinophils correlated well with bronchial responsiveness to nonspecific stimuli [15]. Therefore, this experimental system seems to be useful to analyze whether or how Th2 cells utilize chemokine/chemokine receptor interactions to induce eosinophilic inflammation.…”
Section: Introductionmentioning
confidence: 99%